Comparison of IRI-2012 with JASON-1 TEC and incoherent scatter radar observations during the 2008–2009 solar minimum period. (August 2016) - Ji, Eun-Young; Jee, Geonhwa; Lee, Changsup
Abstract: The 2008–2009 solar minimum period was unprecedentedly deep and extended. We compare the IRI-2012 with global TEC data from JASON-1 satellite and with electron density profiles observed from incoherent scatter radars (ISRs) at middle and high latitudes for this solar minimum period. Global daily mean TECs are calculated from JASON-1 TECs to compare with the corresponding IRI TECs during the 2008–2009 period. It is found that IRI underestimates the global daily mean TEC by about 20–50%. The comparison of global TEC maps further reveals that IRI overall underestimates TEC for the whole globe except for the low-latitude region around the equatorial anomaly, regardless of season. The underestimation is particularly strong in the nighttime winter hemisphere where the ionosphere seems to almost disappear in IRI. In the daytime equatorial region, however, the overestimation of IRI is mainly due to the misrepresentation of the equatorial anomaly in IRI. Further comparison with ISR electron density profiles confirms the significant underestimation of IRI at night in the winter hemisphere.